2006
DOI: 10.1128/jb.188.8.3116-3120.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Biofilm Formation and Motility Associated with Lipopolysaccharide/Exopolysaccharide-Coupled Biosynthetic Genes inStenotrophomonas maltophilia

Abstract: Stenotrophomonas maltophilia WR-C is capable of forming biofilm on polystyrene and glass. The lipopolysaccharide/exopolysaccharide-coupled biosynthetic genes rmlA, rmlC, and xanB are necessary for biofilm formation and twitching motility. Mutants with mutations in rmlAC and xanB display contrasting biofilm phenotypes on polystyrene and glass and differ in swimming motility.Microorganisms can develop biofilms or clogging mats, causing the failure of septic tanks, systems for on-site wastewater disposal. If wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 42 publications
4
112
0
1
Order By: Relevance
“…Mutants for the glucose-1-phosphate thymidyltransferase rmlA gene and for the cis-11-methyl-2-dodecenoic acid rpfF gene were reported to decreases biofilm formation [12,13]. Further, the spgM gene, encoding a bifunctional enzyme with both phosphoglucomutase (PGM) and phosphomannomutase activities, is involved in biofilm-forming ability in S. maltophilia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mutants for the glucose-1-phosphate thymidyltransferase rmlA gene and for the cis-11-methyl-2-dodecenoic acid rpfF gene were reported to decreases biofilm formation [12,13]. Further, the spgM gene, encoding a bifunctional enzyme with both phosphoglucomutase (PGM) and phosphomannomutase activities, is involved in biofilm-forming ability in S. maltophilia [14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has recently been demonstrated that various Lysobacter-type species have the ability to readily form biofilms on various substrates. These species include Stenotrophomonas maltophilia, Xylella fastidiosa and Xanthomonas axonopodis [40][41][42]. Therefore, it is unsurprising that these species were identified on the prostheses of the patients in our study.…”
Section: Discussionmentioning
confidence: 75%
“…While other groups have shown that the LPS core oligosaccharide is essential for biofilm formation by E. coli, Klebsiella pneumoniae, and S. maltophilia (42)(43)(44), our LPS core mutant, strain CG3, was still able to produce biofilms similarly to the parental A. pleuropneumoniae strain (Fig. 1).…”
Section: Discussionmentioning
confidence: 88%
“…citri O-antigen LPS) impaired biofilm formation on plastic surfaces and host plant leaves (41). The formation of Stenotrophomonas maltophilia biofilms requires an intact LPS, and a mutation in O-antigen biosynthesis affects EPS production and biofilm formation (42). Clifford and coworkers showed that the O antigen of Xylella fastidiosa is needed for biofilm maturation and surface attachment (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation